The Influence of Alkalinity in Oxygen Delignification of Soda/AQ Pulp From Old Corrugated Container - Mohammad ali Azad far (Regional Information Center for Science and Technology (RICeST), 2011)
The influence of oxygen delignification as an environmental friendly process, was investigated on Soda/AQ pulp from Old Corrugated Container (OCC) fibers. Oxygen delignification at four levels of alkali (2, 3, 4 and 6% based on OD weight of pulp) has been applied and the optimum alkalinity to reach optimum Kappa no, yield and brightness, opacity and strength based on 60 g/m2 hand sheets were determined. The results indicated that application of oxygen delignification marginally reduced the opacity of the pulp. Tear strength increased where as tensile and burst strength decreased. Based on the comparison of the data from oxygen delignified pulp, it is concluded that oxygen can be utilized to improve the properties of soda-AQ pulp from OCC prepared for bleaching step. Carbohydrates are preserved while removing lignin. Normalized equations revealed that oxygen delignification at 3% alkali produced the best results.